2018
DOI: 10.1002/fee.1963
|View full text |Cite
|
Sign up to set email alerts
|

Historical and potential future importance of large whales as food for polar bears

Abstract: Polar bears (Ursus maritimus) are expected to be adversely impacted by a warming Arctic due to melting of the sea‐ice platform from which they hunt ice‐breeding seals. We evaluated the hypothesis that scavenging on stranded large whale carcasses may have facilitated polar bear survival through past interglacial periods during which sea‐ice was limited by analyzing: (1) present‐day scavenging by polar bears on large whale carcasses; (2) energy values of large whale species; and (3) the ability of polar bears, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(48 citation statements)
references
References 59 publications
(105 reference statements)
1
37
0
Order By: Relevance
“…As sea-ice loss continues it is uncertain how much additional time polar bears can spend in poor foraging habitats (e.g., land, sea ice over less-productive waters of the polar basin) 57 , 58 without experiencing negative nutritional and demographic effects. The availability of supplemental nutrition in the form of stranded carcasses of gray whales ( Eschrichtius robustus ), bowhead whales ( Balaena mysticetus ), and other marine mammals along the coastlines of the CS region may become increasingly important as sea-ice loss continues, although these resources are unlikely to compensate for the effects of sea-ice loss in the long term 59 .…”
Section: Discussionmentioning
confidence: 99%
“…As sea-ice loss continues it is uncertain how much additional time polar bears can spend in poor foraging habitats (e.g., land, sea ice over less-productive waters of the polar basin) 57 , 58 without experiencing negative nutritional and demographic effects. The availability of supplemental nutrition in the form of stranded carcasses of gray whales ( Eschrichtius robustus ), bowhead whales ( Balaena mysticetus ), and other marine mammals along the coastlines of the CS region may become increasingly important as sea-ice loss continues, although these resources are unlikely to compensate for the effects of sea-ice loss in the long term 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Bowhead whales (Balaena mysticetus) are harvested for subsistence in the SB and in other subpopulations including Foxe Basin (FB), wherein bowhead remains washing ashore have also been attributed to predation by killer whales (Orcinus orca) in recent years (Galicia et al, 2016). These remains are foraged upon by polar bears in both subpopulations (Atwood et al, 2016;Galicia et al, 2016), and elsewhere where beached whales are found (Laidre, Stirling, Estes, Kochnev, & Roberts, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Admittedly, little is known about the foraging success of bears using the deteriorating sea ice over the continental shelf in the summer or its potential carrying capacity. Nevertheless, land bears also may have access to beach‐cast marine mammal carcasses (Bentzen et al , Laidre et al ) and, in Alaska, subsistence‐harvested bowhead whale carcasses beginning in late August (Rogers et al , Whiteman et al 2017 b ). We found that all three of the land bears in this study visited bowhead whale harvest sites in August and September.…”
Section: Discussionmentioning
confidence: 99%
“…In view of this, the energetic benefit at these sites likely offsets the costs to reach them (Laidre et al ). For example, Laidre et al () estimated that a whole bowhead whale carcass would provide the nutritional equivalent of 1,300 ringed seals for a polar bear. Although much of the meat and blubber are subsistence harvested at these sites (Miller et al ), considerable remains exist and would benefit energetic balance.…”
Section: Discussionmentioning
confidence: 99%